Partial Alignment of Astrometric Position Excursions of International Celestial Reference Frame Quasars with Radio Jet Structures - Valeri V. Makarov; Phil Cigan; David Gordon; Megan C. Johnson; Christopher DiLullo; Sébastien Lambert (The Astrophysical Journal Letters)
Published analyses of very long baseline interferometry data for the sources included in the third International Celestial Reference Frame catalog have revealed object-specific, excess astrometric variability and quasi-coherent trajectories as functions of time. A fraction of these sources show markedly elongated distributions of positions on the sky measured with diurnal observations. Here we apply a novel statistical and data-processing method to the diurnal position measurements stretching over 40 yr to quantify the degree of elongation and its position angle, for each source with more than 200 data points. We find that 49% of the examined sources have distribution elongations in excess of 1.3. Robust uncertainties of the directions of maximal astrometric dispersion are computed by the bootstrapping method, and the results are compared with a larger catalog of radio jet directions by A. V. Plavin et al. ( 2022 ). Nearly one-half of the sources with smaller position angle uncertainties are found to have astrometric position excursions from their mean positions aligned with the radio jet structures within ±30°.